Changes in the Reward-based Crowdfunding Project and Fundraiser by COVID-19 Pandemic - Yoshihiro UCHIDA (AAOS Transactions)
The Japanese Reward-based crowdfunding market expanded significantly with the COVID-19 pandemic. This market expansion potentially altered the profile of fundraisers and project tendencies. This study empirically analyzed changes in fundraisers and projects associated with the COVID-19 pandemic, utilizing data from the Japanese crowdfunding platform, propensity score, and logistic regression models. The results suggest that there are changes in project tendencies, notwithstanding the changes in funders due to the COVID-19 pandemic. Specifically, there are indications that crowdfunding is increasingly being utilized as a means for general business development, with new fundraisers entering with established recognition and brand that are independent of crowdfunding platforms. Additionally, the results suggest that the impacts of the COVID-19 pandemic differed by project category.